Resistance mechanisms in Lycopersicon spp. to tomato powdery mildew (Oidium neolycopersici) - A. Lebeda; B. Mieslerová; L. Luhová; K. Mlíčková (Plant Protection Science, 2002)
Limited information on the resistance mechanisms in Lycopersicon spp. to Oidium neolycopersici is still available. Macroscopically the resistance is characterized by a very low amount of mycelium development and a lack of sporulation. The leaf surface did not effectively inhibite conidium germination, however significant differences in germ tube and appressorium development were recorded. A large variation was observed in host tissue response. The prevailing resistance mechanism was hypersensitivity (HR). Considerable changes of peroxidase and catalase activities during pathogenesis were detected among tested wild Lycopersicon spp. There was positive correlation between increasing of peroxidase activity and extent of necrosis. Histochemistry showed large differences in production of superoxid ions, H2O2 and peroxidase in Lycopersicon spp. with various level of resistance.